Harlow : A Novel - Armand, David, 1980- (Book collections on Project MUSE., 2013)
"Harlow tells the story of eighteen-year-old Leslie Somers, who trudges his way through the dark Louisiana backwoods one winter in search of his father. As he walks through the woods, Leslie thinks of the other male role models in his life: the men who took him hunting and fishing, the men who mistreated him. Since Leslie has been forsaken by his mother, he can only imagine a life with this man he has never met: his father, Harlow Cagwin. But when Leslie finally finds Harlow, the man is not what the boy had expected. The two end up on a crash course toward destruction, crime, and twisted relationships that will leave one of them dead, the other a hardly recognizable version of his former self."--Publisher's website.